The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1152/ajpheart.1996.271.6.h2254
|View full text |Cite
|
Sign up to set email alerts
|

In vivo inhibition of transcellular water channels (aquaporin-1) during acute peritoneal dialysis in rats

Abstract: During peritoneal dialysis (PD), a major portion of the osmotically induced water transport to the peritoneum can be predicted to occur through endothelial water-selective channels. Aquaporin-1 (AQP-1) has recently been recognized as the molecular correlate to such channels. Aquaporins can be inhibited by mercurials. In the present study, HgCl2 was applied locally to the peritoneal cavity in rats after short-term tissue fixation, used to protect the tissues from HgCl2 damage. Dianeal (3.86%) was employed as di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 0 publications
2
84
0
Order By: Relevance
“…Water equilibration across the vasa recta may also play a critical role in avoiding the disruption of the osmotic gradient established by the countercurrent exchanger. It should also be mentioned that the demonstrated role of aquaporins, including AQP1 for peritoneal transport of water in experimental peritoneal dialysis (19), was also later confirmed in AQP1-deficient mice (259).…”
Section: A Aqp1mentioning
confidence: 95%
See 1 more Smart Citation
“…Water equilibration across the vasa recta may also play a critical role in avoiding the disruption of the osmotic gradient established by the countercurrent exchanger. It should also be mentioned that the demonstrated role of aquaporins, including AQP1 for peritoneal transport of water in experimental peritoneal dialysis (19), was also later confirmed in AQP1-deficient mice (259).…”
Section: A Aqp1mentioning
confidence: 95%
“…Functional studies were performed using isolated perfused descending vasa recta briefly fixed with glutaraldehyde. This fixation was performed to eliminate the cellular toxicity of mercurials, and it has been shown in collecting duct (124), toad urinary bladders (241), and peritoneum (19) that fixation at least partially maintains the osmotic water permeability. The fixed descending vasa recta displayed a marked sensitivity for mercurials on the transendothelial water permeability, confirming that AQP1 at this site may play a significant role for water transport.…”
Section: A Aqp1mentioning
confidence: 99%
“…These large pores account for only 0.01% of the total population of capillary pores and transport across them occurs by hydrostatic pressure-driven unidirectional filtration from the plasma to the peritoneal cavity. In addition, the capillary wall has a high permeability to osmotic water transport through ultrasmall, water-only pores of radius ~2.5 Å present in the endothelial cell membrane (13,14).…”
Section: Structure Of the Peritoneal Membranementioning
confidence: 99%
“…Of interest is the location of the side chain of a cysteine residue (Cys189) in the pore, explaining why the water permeability mediated by AQP1 is inhibited by mercury compounds (23). The functional relevance of AQP1 for PD was first suggested by ex vivo inhibition of peritoneal water permeability by HgCl2 in a rat model (13). Studies conducted in the Aqp1 knock-out (KO) mice demonstrated that the osmotically-driven water transport across the peritoneal membrane was significantly decreased in Aqp1-/-mice, as compared with wild-type littermates (26).…”
Section: Aquaporin-1 Is the Ultrasmall Pore Of The Peritoneal Membranementioning
confidence: 99%
“…Kinetic models of peritoneal dialysis postulate distinct classes of 'pores' that transport water and solutes to various extents, including an ultrasmall, 'water-only' pore. Early expression studies and measurements of mercurial inhibition of peritoneal water transport suggested that the water-only pore is AQP1 (44), which has been localized to capillary endothelia and mesangium near the peritoneal luminal surface.…”
Section: Role Of Aquaporins In Peritoneal Fluid Transportmentioning
confidence: 99%